2012
DOI: 10.1021/ic300457z
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Manganese-Porphyrin-Catalyzed Epoxidation and C–H Hydroxylation with Hydrogen Peroxide in Water/Methanol Solutions

Abstract: The asymmetric epoxidation of alkene and hydroxylation of arylalkane derivatives by H(2)O(2) to give optically active epoxides (enantiomeric excess (ee) up to 68%) and alcohols (ee up to 57%), respectively, were carried out in water/methanol solutions using chiral water-soluble manganese porphyrins as catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 37 publications
2
69
0
Order By: Relevance
“…However, Simonneaux and co-workers reported in 2012 the enantioselective epoxidation of styrene derivatives using H2O2 (ee up to 68%), in water-methanol solutions using chiral water-soluble manganese and iron porphyrins as catalysts (Scheme 5) [43,44]. They also studied various factors Optically active epoxides obtained from the catalytic enantioselective epoxidation of alkenes are important intermediates in asymmetric synthesis, since these compounds are very useful for the synthesis of chirons with up to two contiguous stereogenic centres [37,38].…”
Section: Epoxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Simonneaux and co-workers reported in 2012 the enantioselective epoxidation of styrene derivatives using H2O2 (ee up to 68%), in water-methanol solutions using chiral water-soluble manganese and iron porphyrins as catalysts (Scheme 5) [43,44]. They also studied various factors Optically active epoxides obtained from the catalytic enantioselective epoxidation of alkenes are important intermediates in asymmetric synthesis, since these compounds are very useful for the synthesis of chirons with up to two contiguous stereogenic centres [37,38].…”
Section: Epoxidationmentioning
confidence: 99%
“…However, Simonneaux and co-workers reported in 2012 the enantioselective epoxidation of styrene derivatives using H 2 O 2 (ee up to 68%), in water-methanol solutions using chiral water-soluble manganese and iron porphyrins as catalysts (Scheme 5) [43,44]. They also studied various factors which affect the catalytic epoxidation of olefins and found that the water present in the methanol is quite useful [44].…”
Section: Epoxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of hydrogen peroxide as oxidant in Mn-catalyzed epoxidation was reviewed recently by Krishnan et al 169 Being similar to iron, the manganese-porphyrin complexes were found to be able to catalyze the asymmetric epoxidation of unfunctionalized olefins with aqueous hydrogen peroxide as oxidant but the substrate scope was relatively narrow and the level of the asymmetric induction was only moderate. 170 In 2011, Bryliakov et al discovered that a Mn complex with a tetradentate aminopyridine ligand featuring a cyclohexanediamine scaffold was an efficient catalyst for the enantioselective epoxidation of olefins using aqueous hydrogen peroxide as the terminal oxidant and a large excess amount of acetic acid as additive, although the products were obtained in lower enantioselectivities. The same research group also developed a chiral tetradentate aminopyridine ligand based on a bis-pyrrolidine structure, which turned out to be a good ligand for the Mn-catalyzed H 2 O 2 -mediated asymmetric epoxidation of electron-deficient olefins, thereby yielding the products in moderate-to-good enantioselectivities.…”
Section: Epoxidationmentioning
confidence: 99%
“…We also described recent chiral epoxidation of alkenes in water/methanol solutions using H 2 O 2 as an oxidant catalyzed by new optically active water-soluble iron [43] and manganese porphyrins [44] (Figure 5). A chiral water-soluble Halterman porphyrin, due to the presence of four sulfonate groups at the para-position, was previously reported by our group and used for the chiral recognition of amino acids [18] and catalytic carbene transfer in water [45].…”
Section: Asymmetric Oxidation Reactionsmentioning
confidence: 99%